Gender, Race, and (Un)Ethical Behavior: Perceptions from Within the Federal Bureaucracy - Francesca M. Bove; Matthew J. Uttermark; Lauren A. Dula (Journal of Social Equity and Public Administration)
How do bureaucrats with doubly underrepresented identities—specifically, women of color—navigate ethics within their workplace? Leveraging an intersectionality framework, we expect that women of color bureaucrats will have lower perceptions of their ethical environment and be more likely to witness unethical behavior versus men of color, white men, and white women employees. Using the Merit Principles Survey, we model gender and race as an interaction finding women of color report higher rates of observing unethical behavior and are more personally affected by the unethical behaviors of their superiors and colleagues. Our findings indicate that recent methodological recommendations to advance our understanding of doubly underrepresented identities provide a more detailed understanding of the barriers women of color face. For practitioners, our findings suggest reevaluating best practices to cultivate an ethical workplace.